Fertility preservation and management of pregnancy in melanoma patients requiring systemic therapy - Hassel, Jessica C.; Livingstone, E.; Allam, J. P.; Behre, H. M.; Bojunga, J.; Klein, H. H.; Landsberg, J.; Nawroth, F.; Schüring, A.; Susok, L.; Thoms, K. M.; Kiesel, L.; et al. (ESMO open, 2021)
Melanoma is one of the most common cancers in adolescents and adults at fertile age, especially in women. With novel and more effective systemic therapies that began to profoundly change the dismal outcome of melanoma by prolonging overall survival, the wish for fertility preservation or even parenthood has to be considered for a growing portion of melanoma patients—from the patients' as well as from the physicians' perspective. The dual blockade of the mitogen-activated protein kinase pathway by B-Raf proto-oncogene serine/threonine kinase and mitogen-activated protein kinase inhibitors and the immune checkpoint inhibition by anti-programmed cell death protein 1 and anti-cytotoxic T-lymphocyte-associated protein-4 monoclonal antibodies constitute the current standard systemic approaches to combat locally advanced or metastatic melanoma. Here, the preclinical data and clinical evidence of these systemic therapies are reviewed in terms of their potential gonadotoxicity, teratogenicity, embryotoxicity and fetotoxicity. Recommendations for routine fertility and contraception counseling of melanoma patients at fertile age are provided in line with interdisciplinary recommendations for the diagnostic work-up of these patients and for fertility-protective measures. Differentiated recommendations for the systemic therapy in both the adjuvant and the advanced, metastatic treatment situation are given. In addition, the challenges of pregnancy during systemic melanoma therapy are discussed.
Gesehen am 28.01.2022